A calorimetric study of the interaction between Brachiaria platyphylla and soil microbial activity - Schabes, Fanny Isabel (2011)
Recently, lemon tree plantations in Tucumán province, Argentina were invaded with the weed Brachiaria platyphylla (broadleaf signalgrass). In order to understand the mechanisms involved with its propagation, soils collected from the invaded (IS), not yet invaded (NIS) and from an adjacent forest soil (FS) were comparatively studied by chemical and calorimetric techniques. Also the ethyl acetate (EtOAc) extract of aerial parts and roots as well as the methanol (MeOH) extract of aerial parts were studied in their interaction with soil. Two probable factors involved with B. platyphylla invasibility were found. The first deals with the quality of the IS that resembled more the indigenous FS than the NIS. The microbial quotient (Cmic/Corg) was higher for IS than for NIS. Also, the calorespirometric quotient (p/rCO2) was lower for the former soil indicating a greater microbial mineralizing activity. The second factor deals with the effect of the organic extracts on soil. The EtOAc extract of aerial parts of B. platyphylla showed antimicrobial and allelopathic effects that could be attributed to its phenolic content. However, the MeOH extract of aerial parts and EtOAc extract of roots seemed to induce the activity of phenol degrading bacteria. Therefore, the phenolic content of this species would not be a problem for itself although they seem to act as allelochemicals for native species.